COMBINATION OF WHOLE BRAIN RADIOTHERAPY WITH DIFFERENT FRACTION AND CONCOMITANT CAPECITABINE IN BRAIN METASTASIS BREAST CANCER - RUDIYO, YEOH; ISKANDAR, JAPARDI; AZNAN, LELO; SUSWORO, SUSWORO; JACUB, PANDELAKI; ADANG, BACHTIAR; MUHAMMAD, ICHWAN; SUZY, INDHARTY; JULI, JAMNASI; WILLIAM, OMAR (International Journal of Current Pharmaceutical Research, 2020)
Objective: Breast cancer is the second most frequent cancer worldwide. The main therapeutic modality for breast cancer with brain metastasis is radiation. Whole Brain Radiotherapy (WBRT) is a regional treatment that provides moderate doses of radiotherapy to all brain tissue. Capecitabine was found to be effective for the treatment of breast cancer with metastasis. This study aims to determine the effectiveness of WBRT on the response of breast cancer brain metastatic lesions combined with capecitabine administration. Methods: This study uses a prospective, randomized-blind cohort analytic study approach. Subjects were randomized into two groups by giving different fraction of WBRT and capecitabine. Subjects were evaluated 4 w post-radiation. Data on differences in patient responses in the two treatment groups were analyzed. Results: A total of 23 breast cancer patients with brain metastasis participated in this study. Group I (WBRT 10x3Gy + capecitabine 1000 mg/m2/b.i.d) obtained results of 5 (45.5%) out of 11 are responding to therapy. Whereas in group II (WBRT 20x2Gy + capecitabine1000 mg/m2/b.i.d) found 11 (91.7%) out of 12 patients responded to therapy. The results of statistical analysis showed that there were significant differences between the two groups with a value of P = 0.027. Conclusion: Giving capecitabine and WBRT with 20x2Gy gives a better response both clinically and statistically